Operative optimization of normal modes of non-uniformity electric networks with long-distance power transmissions - Кулик, Владимир Владимирович (Eastern-European Journal of Enterprise Technologies, 2014)
An improved mathematical model of the non-uniformity of the electrical system (ES) with the long-distance AC power transmission was presented. A method of forming the control actions for the control devices of such system, the implementation of which allows to ensure maximum power transmission efficiency was proposed. The features of the hardware and software implementation of local management of ES control devices, which provides the benefits of centralized management were given. Electrical systems are not optimal in terms of electricity consumption in its production, transportation and distribution. One of the main reasons for non-optimal states of the ES is their non-uniformity. Based on the above mathematical model of non-uniformity of electric networks taking into account the operation features of long-distance power transmission lines it was shown that for such networks because of the instability of the longitudinal and transverse parameters, their uniform state cannot be practically achieved. Thus, ensuring the optimality of their modes requires using appropriate automatic control systems. To solve the problem of determining the optimal control laws of ES coupling transformers taking into account the features of their impact on the process of electricity transmission and distribution in electric networks with long-distance power transmissions, a mathematical model of optimal electromotive forces of imbalance, as well as the method of determining the optimal transformation ratios of control devices taking into account the wave properties of long-distance PTL, as well as the effect of unbalanced ratios of transformation of coupling transformers and voltage regulation in ES power centers, were proposed. This improvement allows to make better decisions in the optimal control of power flows and voltage in the ES.